Protección a la mujer en estado de gestación frente al despido intempestivo en la legislación laboral ecuatoriana - Toapanta Pujos, Segundo Eduardo (2015)
To abruptly terminate the employment contract have consequences, economic major, but human they should not be put aside, and even if a woman in gestation is discharged unexpectedly, as they are essential for overcome these setbacks, and if there is no payment of the obligations which by law must be presented logically claim your payment, by the party concerned, although many times the worker is injured, we can not help thinking that many Sometimes the employer is also harmed by actions that are harmful, preventing thereby generating employment, efforts must be made to the defense of all that make the relationship work, well now the more protected the minor conditions or situations economic, physical and cultural, as in the present case the woman pregnant, but the rules are clear and we play with them, if the employer fires unexpectedly and does not pay that by law should you ever need to do, and surcharges Act with interest and fees, and sometimes in a single payment, which makes the situation more difficult. Given this situation and no doubt in the case of unfair dismissal lawsuit by legal logic tells us that women in gestation, when demand should have all the necessary evidence to prove what was stated in the same should contain essential elements for this purpose.